Distribution of 14C-Photosynthetate in the Shoot of Vitis vinifera L. cv Cabernet Sauvignon II. The Effect of Partial Defoliation - HUNTER, J.J.; VISSER, J.H. (South African Journal of Enology and Viticulture, 2017)
The effect of partial defoliation of Vitis vinifera L. cv Cabernet Sauvignon on the distribution of photosynthetates, originating in leaves in different positions on the shoot at berry set, pea size, veraison and ripeness stages, was investigated. Partial defoliation (33% and 66%) resulted in a higher apparent photosynthetic effectivity for all the remaining leaves on the shoot. The pattern of distribution of photosynthetates would seem to stay the same between the defoliation treatments. The control vines were found to carry excess foliage. Optimal photosynthetic activity of all the leaves on the vine was therefore not reached.